2001
DOI: 10.1111/0272-4332.211101
|View full text |Cite
|
Sign up to set email alerts
|

Limits of Knowledge and the Limited Importance of Trust

Abstract: Perceived risk and related attitudes have been implicated as major factors in many of the difficult policy problems that face modern society (nuclear power, genetically modified food, etc). Experts often argue that no or very small risks are involved; people are still worried. Why? The standard answer is lack of trust. Data on trust and risk perception, however, point to only a weak relationship between the two ( r approximately 0.3). It is suggested here that the reason for the surprisingly minor importance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
125
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(138 citation statements)
references
References 21 publications
8
125
1
4
Order By: Relevance
“…Some studies have reported strong relationships between related concepts (e.g., trust and perceived risk) (Flynn et al 1992. Findings here, however, were consistent with research reporting relatively weak relationships (e.g., Needham and Vaske 2008;Sjöberg 2000bSjöberg , 2001Viklund 2003). Given that most of the variance in these concepts remains unexplained by trust, other attributes such as knowledge, control, and newness may also contribute to respondents' perceptions (e.g., Fischhoff et al 1978, Sjöberg 2000a).…”
Section: Theoretical Implicationssupporting
confidence: 80%
See 1 more Smart Citation
“…Some studies have reported strong relationships between related concepts (e.g., trust and perceived risk) (Flynn et al 1992. Findings here, however, were consistent with research reporting relatively weak relationships (e.g., Needham and Vaske 2008;Sjöberg 2000bSjöberg , 2001Viklund 2003). Given that most of the variance in these concepts remains unexplained by trust, other attributes such as knowledge, control, and newness may also contribute to respondents' perceptions (e.g., Fischhoff et al 1978, Sjöberg 2000a).…”
Section: Theoretical Implicationssupporting
confidence: 80%
“…People may trust a managing agency, but feel that potential risks (e.g., the ability to contain a prescribed burn) are beyond agency control (Sjöberg 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of health risk assessment, Johnson and Slovic (1995) look at the problem of conveying uncertainties and the consequences for risk perception and trust. Sjoberg (2001) reports that trust and risk perception bear only a weak relationship because people believe that there are limits to what even experts can know. In almost all these cases, the risks under consideration are physical health or workplace risks.…”
Section: Discussionmentioning
confidence: 99%
“…Una primera perspectiva, basada en la imagen corriente de la ciencia, explica las actitudes públi-cas a partir del modelo de déficit cognitivo, para lo que se ha servido de una ciencia abstracta y descontextualizada, y ha presupuesto una imagen normativa de cultura científica asociada a la imagen de individuo científicamente informado (Wolpert, 1992); el nivel de conocimiento del vocabulario y método cientí-fico permite entender, al establecer una correlación, el nivel de legitimación de las políticas científicas. Mientras tanto, el rol analítico de la perspectiva contextual, desde ángulos diferentes, analiza los contextos en el que interaccionan la ciencia y el público, y las experiencias individuales y colectivas acumuladas, y concluye que las variables de mayor alcance explicativo son aquellos factores relativos a las dimensiones sociales e institucionales de la ciencia, así como la disposición institucional a integrar conocimientos y alternativas en el proceso de innovación y/o regulación (Frewer et alia, 2003;Lassen y Jamison, 2006;Sjöberg, 2001Sjöberg, , 2002.…”
Section: La Paradoja De La Industrializaciónunclassified